MENYONGSONG 25 TAHUN SISTER CITY JAKARTA – TOKYO - Witarsa Tambunan (Sociae Polites, 2011)
AbstractThe term sister city was originally introduced by Dwight Eisehower to the XII century,which means the town brothers, friendly city. The concept of sister city intends to maximizethe relationship between community members in all corners of the world to be created andmaintain peace. Sister city Jakarta - Tokyo has succeeded in building a positive image ofJakarta as an international city. As an international city, Jakarta has a vision of "Aligningthe city of Jakarta with cities abroad." That is why the cooperation program of sister cityJakarta - Tokyo for the Jakarta Provincial Government is a necessity as a consequence ofJakarta as the Capital of Indonesia Republic and international city. In making the city ofJakarta as the city of city services, through its sister city Quezon City - Tokyo, JakartaProvincial Government to send its agents (HR) to Tokyo to follow the Exchange Program,Apprenticeship and Training Apparatus, to turns knowledge, skill, and attitude towardpositive changing of apparatus, it means improved the quality of human resources so thatits services meet international standards so the city can be a service city. As for thecommunity (people), sister city programs Jakarta - Tokyo has managed to build brotherhoodand friendship through sports and high school student and teacher exchanges.Keywords: Sister City, Service City